Positive electrode active material and method for manufacturing positive electrode active material

By introducing single-crystal particle structures of lithium, oxygen, nickel, manganese or cobalt into the positive electrode active material of lithium secondary batteries, and enriching silicon on the surface layer, the storage stability and electrochemical stability problems are solved, and the high-temperature operation performance of the battery is improved.

CN120435442APending Publication Date: 2025-08-05UMICORE(BE)
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380086368.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-12-16
Filing Date
2023-12-14
Publication Date
2025-08-05

AI Technical Summary

Technical Problem

During the charging and discharging process of existing lithium secondary batteries, the storage stability and electrochemical stability of the positive electrode active material are poor, which affects the battery performance.

Method used

A positive electrode active material containing lithium, oxygen, nickel and at least one metal selected from manganese and cobalt is used, and silicon is enriched on the surface layer to form a single crystal particle structure, inhibit the absorption of water and carbon, and improve hydrophobicity.

Benefits of technology

The storage stability and electrochemical stability of positive electrode active materials are improved, especially maintaining high efficiency under high temperature operation, enhancing the performance of solid-state batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120435442A_ABST
    Figure CN120435442A_ABST
Patent Text Reader

Abstract

The present invention relates to a positive electrode active material for a solid state battery, the positive electrode active material comprising lithium, oxygen, nickel and at least one metal selected from manganese and cobalt, the positive electrode active material having an enriched amount of Si in a surface layer, and the positive electrode active material comprising single crystal particles. The present inventors have unexpectedly found that the positive electrode active material of the present invention improves the storage stability of the positive electrode active material. In particular, a reduction in absorption of water and carbon (or carbon dioxide) is observed by applying a surface layer of Si onto the positive electrode active material. In addition, the positive electrode active material improves the electrochemical stability of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a positive electrode active material for a solid-state battery, comprising Li, M', and O, wherein M' comprises Si. The present invention also relates to a method for producing the positive electrode active material, a solid-state battery comprising the positive electrode active material, and uses of the solid-state battery. Background Art

[0002] With the rapid development of small and lightweight electronic products, electronic equipment, and communication equipment, as well as the widespread demand for electric vehicles in response to environmental concerns, there is a need to improve the performance of secondary batteries used as power sources for these products. Among them, lithium secondary batteries have become a focus as high-performance batteries due to their high energy density and high reference electrode potential.

[0003] During the charging process of a secondary battery, lithium ions are separated from the cathode, transported through the electrolyte, and embedded in the anode, while electrons are separated from the cathode and injected into the anode through an external circuit (charger). During the use or discharge of a secondary battery, lithium ions are separated from the anode, transported through the electrolyte, and embedded in the cathode, while electrons flow through the external circuit to provide electrical work.

[0004] Common cathode active materials are lithium transition metal oxides. During the charge and / or discharge of lithium batteries, the delithiated cathode active materials can slowly react with non-aqueous electrolytes or solid electrolytes, resulting in a gradual decline in the electrochemical performance of lithium batteries using such cathode active materials.

[0005] It has been demonstrated that coating a cathode active material with a metal such as B or Zr (i.e., applying a thin surface layer of metal to the cathode active material such that the amount of the metal is increased in the surface layer) can result in the cathode active material exhibiting greater stability than a corresponding cathode active material without the coating layer.

[0006] Doo et al. (ACS Appl. Energy Mater. 2019, 2, 6246-6253) envisioned the use of polycrystalline LiNi 0.8 Co 0.1 Mn 0.1 The hydrophobic Ni-rich oxide material was obtained after mixing with polydimethylsiloxane and then heating at 230°C to improve the electrochemical stability of the Ni-rich oxide material.

[0007] However, there remains a need to provide positive electrode active materials with improved storage stability and / or improved electrochemical stability.

[0008] An object of the present invention is to provide a positive electrode active material containing Si in order to improve the storage stability and / or improve the electrochemical stability of the positive electrode active material.

[0009] Another object of the present invention is to provide a method for producing the positive electrode active material.

[0010] Another object of the present invention is to provide a secondary battery comprising the positive electrode active material.

[0011] Another object of the present invention is to provide uses of the battery. Summary of the Invention

[0012] In a first aspect, an object of the present invention is achieved by providing a positive electrode active material for a rechargeable battery, the positive electrode active material comprising lithium, oxygen, nickel and at least one metal selected from manganese and cobalt,

[0013] wherein the positive electrode active material has a rich amount of Si in the surface layer; and

[0014] wherein the positive electrode active material comprises single crystal particles.

[0015] In other words, the positive electrode active material of the present invention has a surface layer containing Si.

[0016] The present inventors have unexpectedly discovered that the positive electrode active material of the present invention improves the storage stability of the positive electrode active material. Specifically, by applying a surface layer of Si on the positive electrode active material, a reduction in the absorption of water and carbon (or carbon dioxide) was observed, as shown in the accompanying examples. In addition, the positive electrode active material improves the electrochemical stability of the battery, in particular the electrochemical stability of polymer solid-state batteries, such as those produced by low Q 总量 This indicates high stability of the positive electrode active material powder during high temperature operation. In addition, the positive electrode active material improves the efficiency of the battery, especially the efficiency of the sulfide solid-state battery.

[0017] Without wishing to be bound by any theory, the present inventors believe that the surface layer of Si acts as a hydrophobic surface layer, which inhibits the formation of residual lithium compounds (such as Li2CO3) formed due to the reaction between the lithium present in the positive electrode active material and the water and carbon in the surrounding air, because the hydrophobic surface inhibits the contact between water and the positive electrode active material.

[0018] In another aspect, the present invention provides a method for producing the positive electrode active material.

[0019] In another aspect, the present invention provides a secondary battery comprising the positive electrode active material.

[0020] In another aspect, the present invention provides use of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 XPS peak of Si2p of EX2.1 DETAILED DESCRIPTION

[0022] In the following detailed description, preferred embodiments are described in detail to enable the practice of the present invention. Although the present invention is described with reference to these specific preferred embodiments, it should be understood that the present invention is not limited to these preferred embodiments. On the contrary, the present invention includes many alternatives, modifications and equivalents, which will become apparent from consideration of the following detailed description and accompanying drawings.

[0023] As used herein and in the claims, the term "comprising" should not be interpreted as being limited to the components listed thereafter; it does not exclude other elements or steps. It needs to be interpreted as specifying the presence of the stated characteristics, integers, steps or components mentioned, but does not exclude the presence or addition of one or more other characteristics, integers, steps or components or groups thereof. Thus, the scope of the expression "a composition comprising components A and B" should not be limited to compositions consisting only of components A and B. This means that for the purposes of the present invention, the only relevant components of the composition are A and B. Thus, the terms "comprising" and "including" encompass the more restrictive terms "consisting essentially of" and "consisting of."

[0024] The term "solid-state battery" as used herein and in the claims refers to a cell or battery that includes only solid-state components or substantially solid-state components, such as solid electrodes (eg, anode and cathode) and a solid electrolyte.

[0025] As used herein and in the claims, the term "positive electrode active material" (also referred to as cathode active material) is defined as a material that is electrochemically active in the positive electrode or cathode. By active material, it must be understood that the material is capable of capturing and releasing lithium ions when subjected to a voltage change over a predetermined period of time.

[0026] As used herein, the term "positive electrode" is defined as a material comprising a positive electrode active material and other components that are not electrochemically active, particularly a conductive agent such as carbon black or a binder such as PVDF.

[0027] In the context of the present invention, unless otherwise defined, the terms "solid" and "liquid" are to be understood as referring to solids and liquids under standard temperature and pressure conditions as defined by IUPAC. Accordingly, boiling points and melting points are to be understood as referring to boiling points and melting points at standard atmospheric pressure, i.e., 101325 Pa.

[0028] In the context of the present invention, the carbon content and moisture content (or water content) after exposure are measured by an exposure test in which 40 g of the positive electrode active material is evenly spread on a 95 x 95 mm 2 The experiment was carried out by placing the plates on a plate and placing the plates in a chamber at 30° C. The atmosphere of the chamber was controlled to have a relative humidity level of 50%.

[0029] Positive electrode active material

[0030] In a first aspect, the present invention relates to a positive electrode active material for a solid-state battery, the positive electrode active material comprising lithium, oxygen, nickel and at least one metal selected from manganese and cobalt,

[0031] wherein the positive electrode active material further comprises Si in an amount measured by XPS analysis B of silicon, of which Si B It is expressed as the ratio of the mole fraction of Si to the sum of the mole fractions of Ni, Mn, Co and Si.

[0032] Among them, Si B >0.05, and

[0033] wherein the positive electrode active material comprises single crystal particles.

[0034] A preferred embodiment is the positive electrode active material of the present invention, the positive electrode active material having a carbon content greater than 150 ppm, preferably a carbon content greater than 250 ppm, more preferably a carbon content greater than 300 ppm, based on the total weight of the positive electrode active material. A preferred embodiment is the positive electrode active material of the present invention, the positive electrode active material having a carbon content less than 2000 ppm, preferably a carbon content less than 1850 ppm, more preferably a carbon content less than 1700 ppm, based on the total weight of the positive electrode active material. A preferred embodiment is the positive electrode active material of the present invention, the positive electrode active material having a carbon content in the range of 150 ppm and 2000 ppm, preferably a carbon content in the range of 250 ppm and 1850 ppm, more preferably a carbon content in the range of 300 ppm and 1700 ppm, based on the total weight of the positive electrode active material. A particularly preferred embodiment is a positive electrode active material of the present invention having a carbon content of greater than 500 ppm, preferably a carbon content of greater than 1000 ppm, more preferably a carbon content of greater than 1200 ppm, based on the total weight of the positive electrode active material. A particularly preferred embodiment is a positive electrode active material of the present invention having a carbon content of less than 2000 ppm, preferably a carbon content of less than 1850 ppm, more preferably a carbon content of less than 1700 ppm, based on the total weight of the positive electrode active material. A particularly preferred embodiment is a positive electrode active material of the present invention having a carbon content in the range of 500 ppm and 2000 ppm, preferably a carbon content in the range of 1000 ppm and 1850 ppm, more preferably a carbon content in the range of 1200 ppm and 1700 ppm, based on the total weight of the positive electrode active material. In addition, the carbon content of the positive electrode active material of the present invention reported above was measured before the exposure test. As will be appreciated by those skilled in the art, the carbon content of the positive electrode active material of the present invention is measured using a carbon analyzer. For example, but not limited to the present invention, the carbon content can be measured using a Horiba Emia-Expert carbon / sulfur analyzer.

[0035] In a preferred embodiment of the present invention, the positive electrode active material of the present invention has a carbon uptake of less than 1500 ppm carbon based on the total weight of the positive electrode active material, preferably a carbon uptake of less than 1200 ppm carbon based on the total weight of the positive electrode active material, and more preferably a carbon uptake of less than 1000 ppm carbon based on the total weight of the positive electrode active material. As will be appreciated by those skilled in the art, the carbon uptake is measured after exposure testing.

[0036] A preferred embodiment is the positive electrode active material of the present invention, wherein the positive electrode active material has a water content greater than 10 ppm, preferably a water content greater than 25 ppm, and more preferably a water content greater than 50 ppm, based on the total weight of the positive electrode active material. A preferred embodiment is the positive electrode active material of the present invention, wherein the positive electrode active material has a water content less than 1200 ppm, preferably a water content less than 1000 ppm, and more preferably a water content less than 500 ppm, based on the total weight of the positive electrode active material. A preferred embodiment is the positive electrode active material of the present invention, wherein the positive electrode active material has a water content in the range of 10 ppm and 1200 ppm, preferably a water content in the range of 25 ppm and 1000 ppm, and more preferably a water content in the range of 50 ppm and 500 ppm, based on the total weight of the positive electrode active material. As the skilled person understands, the water content or moisture content is measured by a Karl Metrohm Fischer coulometer.In addition, the water content of the positive electrode active materials of the present invention reported above was measured before the exposure test.

[0037] In a preferred embodiment of the present invention, the positive electrode active material of the present invention has a water absorption of less than 1500 ppm water based on the total weight of the positive electrode active material, preferably a water absorption of less than 1000 ppm water based on the total weight of the positive electrode active material, and more preferably a water absorption of less than 500 ppm water based on the total weight of the positive electrode active material. As will be understood by those skilled in the art, the water absorption is measured after exposure testing.

[0038] A preferred embodiment is the positive electrode active material of the present invention, comprising Li, Ni, Mn, Co, and oxygen, wherein the Ni content is x, wherein 50.0 mol% ≤ x ≤ 98.0 mol% relative to the sum of Ni, Mn, and Co. A more preferred embodiment is the positive electrode active material of the present invention, wherein the Ni content is x ≥ 55.0 mol%, preferably x ≥ 58.0 mol%, and more preferably x ≥ 60.0 mol%, relative to the sum of Ni, Mn, and Co. In a preferred embodiment, the Ni content is x ≤ 90.0 mol%, preferably x ≤ 88 mol%, and more preferably x ≤ 85.0 mol%, relative to the sum of Ni, Mn, and Co. A more preferred embodiment is the positive electrode active material of the present invention, wherein the Ni content x is between 55.0 mol% ≤ x ≤ 90.0 mol%, preferably between 58.0 mol% ≤ x ≤ 88.0 mol%, and more preferably between 60.0 mol% ≤ x ≤ 85.0 mol%, relative to the sum of Ni, Mn, and Co.

[0039] A particularly preferred embodiment is the positive electrode active material of the present invention, comprising Li, Ni, Mn, Co, and oxygen, wherein M' comprises a Ni content of x ≥ 55.0 mol%, preferably x ≥ 58.0 mol%, and more preferably x ≥ 60.0 mol%, relative to the sum of Ni, Mn, and Co. In a particularly preferred embodiment, the Ni content is x ≤ 75.0 mol%, preferably x ≤ 72 mol%, and more preferably x ≤ 70.0 mol%, relative to the sum of Ni, Mn, and Co. A particularly more preferred embodiment is the positive electrode active material of the present invention, wherein the Ni content x, relative to the sum of Ni, Mn, and Co, is between 55.0 mol% and ≤ x and ≤ 75.0 mol%, preferably between 58.0 mol% and ≤ x and ≤ 72.0 mol%, and more preferably between 60.0 mol% and ≤ x and ≤ 70.0 mol%.

[0040] A particularly preferred embodiment is the positive electrode active material of the present invention, comprising Li, Ni, Mn, Co, and oxygen, wherein the Ni content, relative to the sum of Ni, Mn, and Co, is x ≥ 75.0 mol%, preferably x ≥ 78.0 mol%, and more preferably x ≥ 80.0 mol%. In a particularly preferred embodiment, the Ni content, relative to the sum of Ni, Mn, and Co, is x ≤ 92.0 mol%, preferably x ≤ 90 mol%, and more preferably x ≤ 88.0 mol%. A particularly more preferred embodiment is the positive electrode active material of the present invention, wherein the Ni content, x, relative to the sum of Ni, Mn, and Co, is between 75.0 mol% and ≤ x and ≤ 92.0 mol%, preferably between 78.0 mol% and ≤ x and ≤ 90.0 mol%, and more preferably between 80.0 mol% and ≤ x and ≤ 88.0 mol%.

[0041] One preferred embodiment is the positive electrode active material of the present invention, the positive electrode active material comprising Li, Ni, Mn, Co and oxygen, wherein the content of Mn is y, where 0.0 mol% ≤ y ≤ 30.0 mol% relative to the sum of Ni, Mn and Co. A more preferred embodiment is the positive electrode active material of the present invention, wherein the content of Mn is y > 0.0 mol% relative to the sum of Ni, Mn and Co, preferably y ≥ 1.0 mol%, more preferably y ≥ 2.0 mol%. In a more preferred embodiment, the content is y ≤ 20.0 mol% relative to the sum of Ni, Mn and Co, preferably y ≤ 15.0 mol%, and more preferably y ≤ 10.0 mol%. In a more preferred embodiment, the content of Mn is 0.0 mol% < y ≤ 20.0 mol% relative to the sum of Ni, Mn and Co, preferably 1.0 mol% ≤ y ≤ 15.0 mol%, more preferably 2.0 mol% ≤ y ≤ 10.0 mol%.

[0042] A specific preferred embodiment is the positive electrode active material of the present invention, the positive electrode active material comprising Li, Ni, Mn, Co and oxygen, wherein the content of Mn is y > 0.0 mol% relative to the sum of Ni, Mn and Co, preferably y ≥ 5.0 mol%, more preferably y ≥ 10.0 mol%. In a specific preferred embodiment, the content is y ≤ 30.0 mol% relative to the sum of Ni, Mn and Co, preferably y ≤ 25.0 mol%, and more preferably y ≤ 20.0 mol%. In a specific preferred embodiment, the content of Mn is 0.0 mol% < y ≤ 30.0 mol% relative to the sum of Ni, Mn and Co, preferably 5.0 mol% ≤ y ≤ 25.0 mol%, more preferably 10.0 mol% ≤ y ≤ 20.0 mol%.

[0043] One preferred embodiment is the positive electrode active material of the present invention, the positive electrode active material comprising Li, Ni, Mn, Co and oxygen, wherein the content of Co is z, where 0.0 mol% ≤ z ≤ 30.0 mol% relative to the sum of Ni, Mn and Co. In a more preferred embodiment, the content of Co is z > 0.0 mol% relative to the sum of Ni, Mn and Co, preferably z ≥ 1.0 mol%, more preferably z ≥ 2.0 mol%. In a preferred embodiment, the content is z ≤ 20.0 mol% relative to the sum of Ni, Mn and Co, preferably z ≤ 15.0 mol%, and more preferably z ≤ 10.0 mol%. In a preferred embodiment, the content of Co is 0.0 mol% < z ≤ 20.0 mol% relative to the sum of Ni, Mn and Co, preferably 1.0 mol% ≤ z ≤ 15.0 mol%, more preferably 2.0 mol% ≤ z ≤ 10.0 mol%.

[0044] A specific preferred embodiment is the positive electrode active material of the present invention, which contains Li, Ni, Mn, Co and oxygen, wherein the content of Co is z > 0.0 mol%, preferably z ≥ 5.0 mol%, more preferably z ≥ 10.0 mol% relative to the sum of Ni, Mn and Co. In a preferred embodiment, the content is z ≤ 30.0 mol%, preferably z ≤ 25.0 mol%, and more preferably z ≤ 20.0 mol% relative to the sum of Ni, Mn and Co. In a preferred embodiment, the content of Co is 0.0 mol% < z ≤ 30.0 mol%, preferably 5.0 mol% ≤ z ≤ 25.0 mol%, more preferably 10.0 mol% ≤ z ≤ 20.0 mol% relative to the sum of Ni, Mn and Co.

[0045] A highly preferred embodiment is the positive electrode active material of the present invention, which contains Li, Ni, Mn, Co and oxygen, wherein:

[0046] - Ni with a content of x, wherein 50.0 mol% ≤ x ≤ 98.0 mol% relative to the sum of Ni, Mn and Co,

[0047] - Mn with a content of y, wherein 0.0 mol% ≤ y ≤ 30.0 mol% relative to the sum of Ni, Mn and Co,

[0048] - Co with a content of z, wherein 0.0 mol% ≤ z ≤ 30.0 mol% relative to the sum of Ni, Mn and Co, and

[0049] - where x, y and z are measured by ICP - OES.

[0050] As understood by those skilled in the art, the amounts of Li, Ni, Mn and Co in the positive electrode active material are measured by inductively coupled plasma optical emission spectrometry (ICP - OES). For example, but not limited to the present invention, Agilent ICP 720 - ES is used in ICP - OES analysis.

[0051] A more highly preferred embodiment is the positive electrode active material of the present invention, which contains Li, M' and oxygen, wherein M' includes:

[0052] - Ni with a content x between 55.0 mol% ≤ x ≤ 90.0 mol%, preferably between 58.0 mol% ≤ x ≤ 88.0 mol%, more preferably between 60.0 mol% ≤ x ≤ 85.0 mol% relative to the sum of Ni, Mn and Co.

[0053] - Mn with a content of 0.0 mol% < y ≤ 20.0 mol%, preferably 1.0 mol% ≤ y ≤ 15.0 mol%, more preferably 2.0 mol% ≤ y ≤ 10.0 mol%, relative to the sum of Ni, Mn and Co,

[0054] - Co with a content of 0.0 mol% < z ≤ 20.0 mol%, preferably 1.0 mol% ≤ z ≤ 15.0 mol%, more preferably 2.0 mol% ≤ z ≤ 10.0 mol%, relative to the sum of Ni, Mn and Co, and

[0055] - where x, y and z are measured by ICP - OES.

[0056] A highly preferred embodiment is the positive electrode active material of the present invention, which comprises Li, M' and oxygen, where M' includes:

[0057] - Ni with a content of x', where 50.0 mol% ≤ x' ≤ 98.0 mol% relative to M',

[0058] - Mn with a content of y', where 0.0 mol% ≤ y' ≤ 30.0 mol% relative to M',

[0059] - Co with a content of z', where 0.0 mol% ≤ z' ≤ 30.0 mol% relative to M',

[0060] - Si with a content of a', where 0.0 mol% < a' ≤ 5.0 mol% relative to M',

[0061] - D with a content of d', where D is an element other than Li, Ni, Mn, Co, Si and oxygen; where 0.0 mol% ≤ d' ≤ 2.0 mol% relative to M',

[0062] - where x', y', z', a' and d' are measured by ICP - OES, and

[0063] - where x' + y' + z' + a' + d' = 100.0 mol%.

[0064] As understood by those skilled in the art, the amounts of Li and M' (preferably Li, Ni, Mn, Co, D and Si) in the positive electrode active material are measured by inductively coupled plasma optical emission spectrometry (ICP - OES). For example, but not limited to the present invention, Agilent ICP 720 - ES is used in ICP - OES analysis.

[0065] A more preferred embodiment is the positive electrode active material of the present invention, comprising Li, M', and oxygen, wherein M' comprises Ni in an amount x'≥55.0 mol%, preferably x'≥58.0 mol%, and more preferably x'≥60.0 mol%, relative to M'. In a preferred embodiment, the Ni content is x'≤90.0 mol%, preferably x'≤88 mol%, and more preferably x'≤85.0 mol%, relative to M'. A more preferred embodiment is the positive electrode active material of the present invention, wherein the Ni content x' relative to M' is between 55.0 mol% and x≤90.0 mol%, preferably between 58.0 mol% and x'≤88.0 mol%, and more preferably between 60.0 mol% and x'≤85.0 mol%.

[0066] A particularly preferred embodiment is the positive electrode active material of the present invention, comprising Li, M', and oxygen, wherein M' comprises a Ni content of x'≥55.0 mol%, preferably x'≥58.0 mol%, and more preferably x'≥60.0 mol%, relative to M'. In a particularly preferred embodiment, the Ni content is x'≤75.0 mol%, preferably x'≤72 mol%, and more preferably x'≤70.0 mol%, relative to M'. A particularly more preferred embodiment is the positive electrode active material of the present invention, wherein the Ni content x' relative to M' is between 55.0 mol% and x'≤75.0 mol%, preferably between 58.0 mol% and x'≤72.0 mol%, and more preferably between 60.0 mol% and x'≤70.0 mol%.

[0067] A particularly preferred embodiment is the positive electrode active material of the present invention, comprising Li, M', and oxygen, wherein M' comprises Ni in an amount x'≥75.0 mol %, preferably x'≥78.0 mol %, and more preferably x'≥80.0 mol %, relative to M'. In a particularly preferred embodiment, the Ni content is x'≤92.0 mol %, preferably x'≤90 mol %, and more preferably x'≤88.0 mol %, relative to M'. A particularly more preferred embodiment is the positive electrode active material of the present invention, wherein the Ni content x, relative to M', is between 75.0 mol % ≤ x' ≤ 92.0 mol %, preferably between 78.0 mol % ≤ x' ≤ 90.0 mol %, and more preferably between 80.0 mol % ≤ x' ≤ 88.0 mol %.

[0068] A more preferred embodiment is the positive electrode active material of the present invention, the positive electrode active material comprising Li, M' and oxygen, wherein M' comprises Mn having a content of y'>0.0 mol%, preferably y'≥1.0 mol%, more preferably y'≥2.0 mol% relative to M'. In a more preferred embodiment, the content is y'≤20.0 mol%, preferably y'≤15.0 mol%, and more preferably y'≤10.0 mol% relative to M'. In a more preferred embodiment, the content of Mn relative to M' is 0.0 mol%<y'≤20.0 mol%, preferably 1.0 mol%≤y'≤15.0 mol%, more preferably 2.0 mol%≤y'≤10.0 mol%.

[0069] A specific preferred embodiment is the positive electrode active material of the present invention, the positive electrode active material comprising Li, M' and oxygen, wherein M' comprises Mn having a content of y'>0.0 mol%, preferably y'≥5.0 mol%, more preferably y'≥10.0 mol% relative to M'. In a specific preferred embodiment, the content is y'≤30.0 mol%, preferably y'≤25.0 mol%, and more preferably y'≤20.0 mol% relative to M'. In a specific preferred embodiment, the content of Mn relative to M' is 0.0 mol%<y'≤30.0 mol%, preferably 5.0 mol%≤y'≤25.0 mol%, more preferably 10.0 mol%≤y'≤20.0 mol%.

[0070] In a more preferred embodiment is the positive electrode active material of the present invention, the positive electrode active material comprising Li, M' and oxygen, wherein M' comprises Co having a content of z'>0.0 mol%, preferably z'≥1.0 mol%, more preferably z'≥2.0 mol% relative to M'. In a preferred embodiment, the content is z'≤20.0 mol%, preferably z'≤15.0 mol%, and more preferably z'≤10.0 mol% relative to M'. In a preferred embodiment, the content of Co relative to M' is 0.0 mol%<z'≤20.0 mol%, preferably 1.0 mol%≤z'≤15.0 mol%, more preferably 2.0 mol%≤z'≤10.0 mol%.

[0071] A particular preferred embodiment is the positive electrode active material of the present invention, the positive electrode active material comprising Li, M' and oxygen, wherein M' comprises Co having a content of z'>0.0 mol%, preferably z'≥5.0 mol%, more preferably z'≥10.0 mol% relative to M'. In a preferred embodiment, relative to M', the content is z'≤30.0 mol%, preferably z'≤25.0 mol%, and more preferably z'≤20.0 mol%. In a preferred embodiment, relative to M', the content of Co is 0.0 mol%<z'≤30.0 mol%, preferably 5.0 mol%≤z'≤25.0 mol%, more preferably 10.0 mol%≤z'≤20.0 mol%.

[0072] As is known to those skilled in the art, the positive electrode active material of the present invention may contain impurities or be doped or coated such that the entire positive electrode active material contains one or more elements other than Li, Ni, Mn, Co, Si, and O, which is reflected in the parameter "D" used herein. A preferred embodiment is the positive electrode active material according to the present invention comprising D, wherein D is at least one element selected from the following: Al, B, Ba, Ca, Ce, Cr, Fe, La, Mg, Mo, Nb, S, Sr, Ti, V, W, Y, Zr, and Zn; preferably Al, B, Ti, Cr, Nb, S, Y, and W; more preferably Al, B, Ti, Nb, and W.

[0073] A preferred embodiment is the positive electrode active material according to the present invention, the positive electrode active material comprising Li, M' and oxygen, wherein M' comprises D having a content of d'>0.0 mol%, preferably d'≥0.25 mol%, more preferably d'≥0.5 mol% relative to M'. In a preferred embodiment, relative to M', the content d'≤1.75 mol%, preferably d'≤1.5 mol%, more preferably d'≤1.25 mol%. In a preferred embodiment, relative to M', the content d is 0.0 mol%<d'≤1.75 mol%, preferably 0.25 mol%≤d'≤1.5 mol%, more preferably 0.5 mol%≤d'≤1.25 mol%.

[0074] In certain preferred embodiments, the positive electrode active material is the positive electrode active material according to the present invention, wherein relative to M', d' = 0.0 mol%.

[0075] One preferred embodiment is the positive electrode active material according to the present invention, the positive electrode active material comprising Li, M' and oxygen, wherein M' includes Si with a content of a'>0.01 mol%, preferably a'≥0.05 mol%, more preferably a'≥0.1 mol% relative to M'. In one preferred embodiment, relative to M', the content a'≤2.0 mol%, preferably a'≤1.0 mol%, more preferably a'≤0.8 mol%. In one preferred embodiment, relative to M', the content a is 0.01 mol%<a'≤2.0 mol%, preferably 0.05 mol%≤a'≤1.0 mol%, more preferably 0.1 mol%≤a'≤0.8 mol%.

[0076] One preferred embodiment is the positive electrode active material of the present invention, the positive electrode active material having a Li / M' ratio, preferably a Li / (Ni + Mn + Co) ratio>0.90, preferably>0.92, more preferably>0.95. One preferred embodiment is the positive electrode active material of the present invention, the positive electrode active material having a Li / M' ratio, preferably a Li / (Ni + Mn + Co) ratio<1.10, preferably<1.08, more preferably<1.05. One preferred embodiment is the positive electrode active material of the present invention, the positive electrode active material having a Li / M' ratio, preferably a Li / (Ni + Mn + Co) ratio in the range of 0.90 - 1.10, preferably in the range of 0.92 - 1.08, more preferably in the range of 0.95 - 1.05. As understood by those skilled in the art, the Li / M' ratio, preferably the Li / (Ni + Mn + Co) ratio, is a molar ratio (mol / mol).

[0077] A highly preferred embodiment is the positive electrode active material according to the present invention having the formula (I):

[0078] Li w2 Ni x2 Mn y2 Co z2 Si a2 D2 d2 O2 (I)

[0079] , where 0.90≤w2≤1.10, preferably 0.92≤w2≤1.08, more preferably 0.95≤w2≤1.05;

[0080] , where 0.55≤x2≤0.90, preferably 0.58≤x2≤0.88, more preferably 0.60≤x2≤0.85;

[0081] , where 0.0<y2≤0.30, preferably 0.05≤y2≤0.25, more preferably 0.10≤y2≤0.20;

[0082] , where 0.0 < z2 ≤ 0.30, preferably 0.05 ≤ z2 ≤ 0.25, more preferably 0.10 ≤ z2 ≤ 0.20;

[0083] , where 0.0001 ≤ a2 ≤ 0.02, preferably 0.0005 ≤ a2 ≤ 0.01, more preferably 0.0001 ≤ a2 ≤ 0.008;

[0084] , where 0.0 ≤ d2 ≤ 0.0175, preferably 0.0 ≤ d2 ≤ 0.015, more preferably 0.0 ≤ d2 ≤ 0.0125, and most preferably d2 is about 0.0;

[0085] where x2 + y2 + z2 + a2 + b2 + d2 = 1.00; and

[0086] where D2 is an element other than Li, O, Ni, Co, Mn, and Si.

[0087] In a preferred embodiment, 0.55 ≤ x2 ≤ 0.75, preferably 0.58 ≤ x2 ≤ 0.72, more preferably 0.60 ≤ x2 ≤ 0.70;

[0088] As is known to those skilled in the art, the positive electrode active material of the present invention may contain impurities or be doped or coated, so that the entire positive electrode active material contains one or more elements other than Li, Ni, Mn, Co, Si, and O, which is reflected in the parameter "D2" used herein. A preferred embodiment is a positive electrode active material according to the present invention containing D2, where D2 is at least one element selected from the following: Al, B, Ba, Ca, Ce, Cr, Fe, La, Mg, Mo, Nb, S, Sr, Ti, V, W, Y, Zr, and Zn; preferably Al, B, Ti, Cr, Nb, S, Y, and W; more preferably Al, B, Ti, Nb, and W.

[0089] Surface layer

[0090] The present invention provides a positive electrode active material according to the present invention, wherein the positive electrode active material contains silicon with a content measured by XPS analysis of Si B of silicon, where Si B is expressed as a ratio of the mole fraction of Si to the sum of the mole fractions of Ni, Mn, Co, and Si, where Si B > 0.05.

[0091] In a preferred embodiment, the positive electrode active material is according to the present invention, where Si B > 0.1, preferably Si B > 0.15, more preferably SiB >0.2. In a preferred embodiment, Si B <5.0, preferably Si B <2.0, more preferably Si B <1.0. In a preferred embodiment, Si B In the range of 0.1 and 5.0, preferably Si B In the range of 0.15 and 2.0, more preferably Si B In the range of 0.2 and 1.0.

[0092] In a particularly preferred embodiment, the positive electrode active material is according to the invention, wherein Si B >0.35, preferably Si B >0.5, more preferably Si B >0.8. In a preferred embodiment, Si B <5.0, preferably Si B <2.0, more preferably Si B <1.0. In a preferred embodiment, Si B In the range of 0.35 and 5.0, preferably Si B In the range of 0.50 and 2.0, more preferably Si B In the range of 0.80 and 1.0.

[0093] In a particularly preferred embodiment, the positive electrode active material is according to the invention, wherein Si B >0.1, preferably Si B >0.15, more preferably Si B >0.2. In a particular preferred embodiment, Si B <1.0, preferably Si B <0.98, more preferably Si B <0.9. In a preferred embodiment, Si B In the range of 0.1 and 1.0, preferably Si B In the range of 0.15 and 0.98, more preferably Si B In the range of 0.2 and 0.9.

[0094] In a particularly preferred embodiment, the positive electrode active material is according to the invention, wherein Si B >0.35, preferably Si B >0.5, more preferably Si B >0.8. In a preferred embodiment, Si B <1.0, preferably Si B<0.98, more preferably Si B <0.9. In a preferred embodiment, Si B In the range of 0.35 and 1.0, preferably Si B In the range of 0.50 and 0.98, more preferably Si B In the range of 0.80 and 0.98.

[0095] In a particularly preferred embodiment, the positive electrode active material is according to the invention, wherein Si B >0.1, preferably Si B >0.15, more preferably Si B >0.2. In a preferred embodiment, Si B <1.0, preferably Si B <0.5, more preferably Si B <0.4. In a preferred embodiment, Si B In the range of 0.1 and 1.0, preferably Si B In the range of 0.15 and 0.5, more preferably Si B In the range of 0.2 and 0.4.

[0096] In one embodiment, the positive electrode active material is according to the present invention, wherein the positive electrode active material further comprises Si in an amount of C of silicon, of which Si C It is expressed as the ratio of the molar fraction of Si to the sum of the molar fractions of Ni, Mn and Co, where Si C >0.05.

[0097] In a preferred embodiment, the positive electrode active material is according to the invention, wherein Si C >0.10, preferably Si C >0.15, more preferably Si C >0.20. In a preferred embodiment, Si C <50.0, preferably Si C <15.0, more preferably Si C <1.0. In a preferred embodiment, Si C In the range of 0.10 and 50.0, preferably Si C In the range of 0.15 and 15.0, more preferably Si C In the range of 0.20 and 1.0.

[0098] In a particularly preferred embodiment, the positive electrode active material is according to the invention, wherein Si C >1.0, preferably SiC >5.0, more preferably Si C >10.0. In a preferred embodiment, Si C <50.0, preferably Si C <40.0, more preferably Si C <30.0. In a preferred embodiment, Si C In the range of 1.0 and 50.0, preferably Si C In the range of 5.0 and 40.0, more preferably Si B In the range of 10.0 and 30.0.

[0099] In a preferred embodiment, the positive electrode active material is according to the present invention, wherein the positive electrode active material has a Si content Si defined as a' / (x'+y'+z'+a') A , wherein the positive electrode active material has a content of Si B Si, of which Si B It is expressed as the ratio of the mole fraction of Si to the sum of the mole fractions of Ni, Mn, Co, Si and Zr, measured by XPS analysis, where the ratio Si B / Si A >5.0.

[0100] In a preferred embodiment, the positive electrode active material is according to the invention, wherein the ratio Si B / Si A >10.0, preferably where the ratio Si B / Si A >15.0, more preferably wherein the ratio Si B / Si A >20.0. In a preferred embodiment, the positive electrode active material is according to the invention, wherein the ratio Si B / Si A <1000.0, preferably where the ratio Si B / Si A <500.0, more preferably wherein the ratio Si B / Si A <100.0. In a preferred embodiment, the positive electrode active material is according to the invention, wherein the ratio Si B / Si A In the range of 10.0 and 1000.0, preferably wherein the ratio Si B / Si A In the range of 15.0 and 500.0, more preferably wherein the ratio Si B / Si A In the range of 20.0 and 100.0.

[0101] In a particularly preferred embodiment, the positive electrode active material is according to the invention wherein the ratio Si B / Si A >80.0. In a particularly preferred embodiment, the positive electrode active material is according to the invention, wherein the ratio Si B / Si A <120.0. In a particularly preferred embodiment, the positive electrode active material is according to the invention, wherein the ratio Si B / Si A In the range of 80.0 and 120.0.

[0102] In the context of the present invention, Si B or Si C is the mole fraction of Si measured within a region of a particle of the positive electrode active material according to the present invention, the region being defined between a first point at the outer edge of the particle and a second point a distance from the first point. The distance between the first and second points is equal to the XPS penetration depth, which is between 1.0 nm and 10.0 nm. Specifically, the penetration depth is the distance along an axis perpendicular to an imaginary line tangent to the outer edge and passing through the first point.

[0103] In the context of the present invention, the outer edge of a particle is the boundary or outer limit that separates the particle from its external environment. Thus, XPS analysis provides the atomic content of elements in the uppermost layer of a particle penetrating to a depth of approximately 10.0 nm from the outer boundary of the particle. The outer boundary of the particle is also referred to as the "surface." For example, but not limited to the present invention, XPS analysis was performed using a Thermo K-α+ spectrometer (Thermo Scientific).

[0104] Within the context of the present invention, atom % means atomic percentage. When expressing concentrations, atom % or "atomic percent" of a given element means what percentage of all atoms in the compound in question are atoms of that element. Furthermore, within the context of the present invention, the symbol atom % is equivalent to mole % or "mole percent."

[0105] As will be understood by the skilled person, the ratio Si defined B / Si A This means that the positive electrode active material of the present invention has a concentrated amount of Si in its surface layer. The surface layer of the positive electrode active material is the uppermost 1 nm to 10 nm of the positive electrode active material. In other words, the positive electrode active material of the present invention includes a surface layer of Si. For example, but not limited to the present invention, the Si compound present in the surface layer of the positive electrode active material is Li2SiO3.

[0106] In the context of the present invention, the positive electrode active material may comprise a first surface layer comprising D, wherein D is at least one element selected from the group consisting of Al, B, Ba, Ca, Ce, Cr, Fe, La, Mg, Mo, Nb, S, Sr, Ti, V, W, Y, Zr and Zn; preferably Al, B, Ti, Cr, Nb, S, Y and W; more preferably Al, B, Ti, Nb and W, wherein the surface layer of Si may be positioned on the first surface layer and / or the first surface layer may be positioned on the surface layer of Si and / or the positive electrode active layer may comprise a mixed surface layer comprising the surface layer of Si and the first surface layer.

[0107] A particularly preferred embodiment relates to a positive electrode active material according to the invention, wherein the positive electrode active material has

[0108] - Si content in the range of 0.10 and 5.0 B Si, preferably Si B In the range of 0.15 and 2.0, more preferably Si B in the range of 0.20 and 1.0; and

[0109] - Si content in the range of 0.10 and 50.0 C Si, preferably Si C In the range of 0.15 and 15.0, more preferably Si C In the range of 0.20 and 1.0.

[0110] A particularly more preferred embodiment relates to a positive electrode active material according to the present invention, wherein the positive electrode active material has

[0111] - Si content in the range of 0.35 and 5.0 B Si, preferably Si B In the range of 0.50 and 2.0, more preferably Si B in the range of 0.80 and 1.0; and

[0112] - Si content ranging between 1.0 and 50.0 C Si, preferably Si C In the range of 5.0 and 40.0, more preferably Si B In the range of 10.0 and 30.0.

[0113] A particularly preferred embodiment relates to a positive electrode active material according to the invention, wherein the positive electrode active material has

[0114] - Si content in the range of 0.10 and 5.0 B Si, preferably Si B In the range of 0.15 and 2.0, more preferably Si B in the range of 0.20 and 1.0; and

[0115] -Ratio Si in the range of 10.0 and 1000.0 B / Si A , preferably wherein the ratio Si B / Si A In the range of 15.0 and 500.0, more preferably wherein the ratio Si B / Si A In the range of 20.0 and 100.0.

[0116] A particularly more preferred embodiment relates to a positive electrode active material according to the present invention, wherein the positive electrode active material has

[0117] - Si content in the range of 0.35 and 5.0 B Si, preferably Si B In the range of 0.50 and 2.0, more preferably Si B is within the range of 0.80 and 1.0; and

[0118] -Ratio Si B / Si A In the range of 80.0 and 120.0.

[0119] A particularly preferred embodiment relates to a positive electrode active material according to the invention, wherein the positive electrode active material has

[0120] - Si content in the range of 0.10 and 5.0 B Si, preferably Si B In the range of 0.15 and 2.0, more preferably Si B In the range of 0.20 and 1.0;

[0121] - Si content in the range of 0.10 and 50.0 C Si, preferably Si C In the range of 0.15 and 15.0, more preferably Si C in the range of 0.20 and 1.0; and

[0122] -Ratio Si in the range of 10.0 and 1000.0 B / Si A , preferably wherein the ratio Si B / Si AIn the range of 15.0 and 500.0, more preferably wherein the ratio Si B / Si A In the range of 20.0 and 100.0.

[0123] A particularly more preferred embodiment relates to a positive electrode active material according to the present invention, wherein the positive electrode active material has

[0124] - Si content in the range of 0.35 and 5.0 B Si, preferably Si B In the range of 0.50 and 2.0, more preferably Si B in the range of 0.80 and 1.0;

[0125] - Si content ranging between 1.0 and 50.0 C Si, preferably Si C In the range of 5.0 and 40.0, more preferably Si B is between 10.0 and 30.0; and

[0126] -Ratio Si B / Si A In the range of 80.0 and 120.0.

[0127] In a preferred embodiment, the particles have a Co content of 0.05 wt% as measured by cross-sectional EDS (CS-EDS) at the edge of the particles. 边缘 Co, of which Co 边缘 Expressed as mol % relative to the sum of the Ni, Mn and Co contents measured by CS-EDS at the edge of the particle, where the particle has a Co content of 中心 Co, of which Co 中心 Expressed as mol % relative to the sum of the Ni, Mn and Co contents measured by CS-EDS at the center of the particle, and where the ratio Co 边缘 / Co 中心 >1.10, preferably Co 边缘 / Co 中心 >1.20, more preferably Co 边缘 / Co 中心 >1.30, most preferably Co 边缘 / Co 中心 >1.50.

[0128] In a preferred embodiment, the particles have an Al content defined as c / (x+y+z+c) AAl, wherein c is the content of Al as measured by XPS, and wherein the positive electrode active material has a content of Al B of Al, of which Al B is determined by XPS analysis, where Al B It is expressed as the ratio of the mole fraction to the sum of the mole fractions of Co, Mn, Ni and Al measured by XPS analysis, where the ratio Al B / Al A >1.0, preferably ratio Al B / Al A >2.0, more preferably a ratio of Al B / Al A >2.5, even more preferably 25 ratio Al B / Al A >3.0, even more preferably a ratio Al B / Al A >3.5, most preferably ratio Al B / Al A >4.0.

[0129] form

[0130] The present invention provides a positive electrode active material according to the present invention, wherein the positive electrode active material comprises single crystal particles.

[0131] In the context of the present invention, a particle is considered to be single crystal if it consists of only one grain or at most five grains, preferably at most three grains, as observed by scanning electron microscopy (SEM) or transmission electron microscopy (TEM), preferably by observing the grain boundaries of the particle. A grain boundary is defined as the interface between two grains in the particle, preferably where the atomic planes of the two grains are arranged in different orientations and meet as a crystallographic discontinuity.

[0132] In certain preferred embodiments of the present invention and in the context of the present invention, the single crystal particles as defined herein are integral particles. As will be appreciated by the skilled artisan, in these certain preferred embodiments, all embodiments relating to single crystal particles also apply to integral particles as defined herein.

[0133] As will be appreciated by those skilled in the art, polycrystalline particles are formed by the agglomeration of 5 or more single crystal particles, preferably 10 or more single crystal particles, and more preferably 50 or more single crystal particles. This can be observed by observing the grain boundaries using appropriate microscopy techniques, such as scanning electron microscopy (SEM). In a post-processing step, such as a heat treatment step, the single crystal particles coalesce into polycrystalline particles.

[0134] Certain preferred embodiments relate to the positive electrode active material of the present invention, comprising single crystalline particles having a primary particle median D50 value of less than 15 mm, preferably less than 10 mm, more preferably less than 5 mm. Certain preferred embodiments relate to the positive electrode active material of the present invention, comprising single crystalline particles having a primary particle median D50 value greater than 1 mm, preferably greater than 2 mm, more preferably greater than 3 mm. Certain preferred embodiments relate to the positive electrode active material of the present invention, comprising single crystalline particles having a primary particle median D50 value between 1 μm and 15 mm, preferably between 2 μm and 10 mm, more preferably between 3 μm and 5 mm. As will be appreciated by those skilled in the art, the particle size distribution (PSD) D50 of the positive electrode active material powder is measured by laser diffraction particle size analysis. Preferably, D50 is defined as the volume average particle size, more preferably the particle size at 50% of the cumulative volume % distribution obtained from a Malvern Mastersizer 3000 with a Hydro MV measurement. For example, but not limiting of the present invention, particle median D50 can be measured using a Malvern Mastersizer 3000.

[0135] As will be understood by those skilled in the art, the single crystal particles have the Si content A 、Si B、 Si C and their corresponding ratios.

[0136] In certain preferred embodiments, the present invention provides a positive electrode active material according to the present invention, wherein the positive electrode active material is a powder comprising single particles and / or secondary particles, wherein each single particle is composed of only one primary particle as observed in the SEM image, and each secondary particle is composed of at least two primary particles and at most twenty primary particles.

[0137] Preferably, at least 30% of the particles, more preferably at least 50% of the particles, constituting the powder observed in the SEM image are single particles and / or secondary particles. The number of primary particles constituting single particles and / or secondary particles is determined in a field of view of at least 45 μm x at least 60 μm (i.e. at least 2700 μm²), preferably at least 100 μm x 100 μm (i.e. at least 10,000 μm²).

[0138] The particles in the image should be evenly distributed to avoid overlap between particles. This can be achieved by pouring a small amount of powder sample into an adhesive attached to the SEM sample holder and blowing air to remove excess powder.

[0139] In the context of the present invention, primary particles are distinguished in SEM images by observing the grain boundaries between the primary particles. A grain boundary is defined as the interface between two primary particles, preferably where the atomic planes of the two primary particles are arranged in different orientations and meet as a crystal discontinuity.

[0140] As will be appreciated by those skilled in the art, polycrystalline particles are formed by the agglomeration of more than 20 primary particles, preferably 50 or more primary particles, and more preferably 100 or more primary particles. Thus, in certain preferred embodiments, the positive electrode active material is a powder comprising polycrystalline particles, wherein each of the polycrystalline particles is composed of more than 20 primary particles, preferably 50 or more primary particles, and more preferably 100 or more primary particles, as observed in an SEM image.

[0141] Preferably, at least 30% of the particles, and more preferably at least 50% of the particles, constituting the powder observed in the SEM image are polycrystalline particles. The number of primary particles constituting polycrystalline particles is determined in a field of view of at least 45 μm x at least 60 μm (i.e., at least 2700 μm²), preferably at least 100 μm x 100 μm (i.e., at least 10,000 μm²). The particles in the image should be evenly distributed to avoid overlap between particles. This can be achieved by pouring a small amount of the powder sample into a binder attached to the SEM sample holder and blowing air through to remove excess powder.

[0142] In another aspect, the present invention provides a single crystal particle-based positive electrode active material for a solid-state battery, the positive electrode active material comprising lithium, oxygen, nickel and at least one metal selected from manganese and cobalt,

[0143] wherein the positive electrode active material further comprises Si in an amount measured by XPS analysis B of silicon, of which Si B It is expressed as the ratio of the mole fraction of Si to the sum of the mole fractions of Ni, Mn, Co and Si.

[0144] Among them, Si B >0.05.

[0145] In a highly preferred embodiment of the single crystal particle based positive electrode active material, all embodiments relating to the positive electrode active material according to the first aspect of the present invention apply mutatis mutandis to the single crystal particle based positive electrode active material. For example, the embodiments relating to Li, M', Si explained herein in the context of the positive electrode active material C 、Si B 、Si A The various embodiments for identification and amount of carbon content also apply to single crystal particle-based positive electrode active materials.

[0146] method

[0147] In a second aspect, the present invention provides a method for producing a positive electrode active material, wherein the method comprises:

[0148] Step a) mixing a lithium transition metal-based oxide compound with a silicon source, and

[0149] Step b) heating the mixture in a furnace under an oxidizing atmosphere at a temperature below 500° C. for a period of time between 1 hour and 20 hours to obtain the positive electrode active material.

[0150] In a highly preferred embodiment of the method for producing the positive electrode active material of the present invention, the positive electrode active material is the positive electrode active material according to the first aspect of the present invention. As the skilled person will appreciate, if the method for producing the positive electrode active material of the present invention results in the positive electrode material according to the first aspect of the present invention, all embodiments relating to the positive electrode active material according to the first aspect of the present invention apply mutatis mutandis to the method for producing the positive electrode active material according to the first aspect of the present invention. For example, the embodiments relating to Li, M', Si explained herein in the context of the positive electrode active material C 、Si B 、Si A The various embodiments for identification and amount of carbon content also apply to the method for preparing the positive electrode active material.

[0151] In a preferred embodiment of the method, the lithium transition metal-based oxide compound comprises Li, M'' and oxygen, wherein M'' comprises Ni, Mn, Co and D, wherein D is at least one element selected from the group consisting of Al, B, Ba, Ca, Ce, Cr, Fe, La, Mg, Mo, Nb, S, Sr, Ti, V, W, Y, Zr and Zn; preferably Al, B, Ti, Cr, Nb, S, Y and W; more preferably Al, B, Ti, Nb and W. Preferably, the lithium transition metal-based oxide used is also typically prepared according to a lithiation process, which is a process in which a mixture of a transition metal oxide precursor and an additional lithium source is heated at a temperature of preferably at least 500 ° C and at most 1000 ° C. Typically, the transition metal precursor is prepared by coprecipitation of one or more transition metal sources, such as salts of the elements Ni, Mn and / or Co, preferably sulfates or nitrates, more preferably sulfates, in the presence of an alkaline compound, such as an alkaline hydroxide, for example sodium hydroxide and / or ammonia. Preferably, the additional lithium source is metallic lithium or a lithium salt, preferably a lithium salt such as LiOH.

[0152] In a preferred embodiment of the method, the Si source is a silicon alkoxide, an alkylalkoxysilane or a polysiloxane, preferably an alkylalkoxysilane or a polysiloxane.

[0153] In a preferred embodiment of the method, the Si source is a silicon alkoxide, preferably SiOR 1 R 2 R 3 R 4 , where R 1 、R 2 、R 3 and R 4 is independently selected from H and C1-C8 alkyl or alkenyl optionally substituted by halide, preferably C1-C4 alkyl, more preferably C1-C2 alkyl. In a more preferred embodiment of the method, the Si source is a silicon alkoxide, i.e. SiOR4 5 , where R 5 is a C1-C8 alkyl or alkenyl group optionally substituted by a halide, preferably a C1-C4 alkyl group, more preferably a C1-C2 alkyl group. In a highly preferred embodiment, the Si source is silicon tetraethoxide.

[0154] In a highly preferred embodiment of the process, the Si source is an alkylalkoxysilane, more preferably R 6 a (R 7 O) b Si, where a=1, 2, or 3, b=1, 2, or 3, a+b=4, and R 6 and R 7 Independently selected from: H and C1-C8 alkyl or alkenyl optionally substituted by halide, preferably C1-C4 alkyl, more preferably C1-C2 alkyl; more preferably R 1 and R 2 is the same alkyl group selected from the group consisting of C1-C8 alkyl or alkenyl groups optionally substituted with halide, preferably C1-C4 alkyl, more preferably C1-C2 alkyl; most preferably the Si source is methyltrimethoxysilane.

[0155] In a highly preferred embodiment, the Si source is a polysiloxane, preferably a polydialkylsiloxane, wherein the alkyl group is selected from C1-C8 alkyl or alkenyl groups optionally substituted with halides, preferably C1-C4 alkyl, more preferably C1-C2 alkyl, more preferably polydimethylsiloxane. In a highly preferred embodiment, the Si source is a polysiloxane, said polysiloxane being a hydroxyl-terminated polydimethylsiloxane or a trimethylsiloxy-terminated polydimethylsiloxane, preferably a hydroxyl-terminated polydimethylsiloxane. The present invention is not limited to polysiloxanes having a specific number average molecular weight M nSpecific polydimethylsiloxanes. Such polymers are commercially available with many different number average molecular weights. Preferably, the hydroxyl-terminated polydimethylsiloxane or trimethylsiloxy-terminated polydimethylsiloxane has a number average molecular weight M between 200 g / mol and 1 000 000 g / mol, preferably between 300 g / mol and 150 000 g / mol, most preferably between 400 g / mol and 10 000 g / mol, such as about 410 g / mol or 4200 g / mol. n .

[0156] In a particularly preferred embodiment, the lithium transition metal-based oxide compound is mixed with the silicon source, in particular when the Si source is a polysiloxane as defined in the present invention, by dry mixing the lithium transition metal-based oxide compound and the silicon source. As will be understood by the skilled person, dry mixing means that no additional solvent is added to the mixture of the lithium transition metal-based oxide compound and the silicon source.

[0157] In a particular preferred embodiment of the method, a silicon source is added to the first liquid, particularly when the silicon source is an alkylalkoxysilane as defined in the present invention, the silicon source is preferably dissolved in the first liquid. Preferably, the first liquid is water. Preferably, the lithium transition metal-based oxide compound with the silicon source added to the first liquid is further mixed with a second liquid, preferably the second liquid comprises water and an alcohol, more preferably the second liquid is a mixture of water and an alcohol. Preferably, the alcohol is methanol, ethanol, propanol, butanol or a mixture thereof, preferably methanol or ethanol, more preferably ethanol. In a preferred embodiment, the weight ratio of alcohol to water (meaning the total content of water present in the first liquid and the second liquid) is between 10:1 and 1:10, preferably between 5:1 and 1:5, more preferably between 2:1 and 1:2. The inventors believe that by adding water to the silicon source of the alkylalkoxysilane as defined in the present invention, the alkylalkoxysilane is hydrolyzed to the corresponding polyalkylsiloxane by a condensation reaction, which is then coated on the positive electrode active material of the present invention by heating step b).

[0158] In a preferred embodiment, the Si content of the silicon source is at least 0.05 wt % relative to the total weight of the positive electrode active material, preferably at least 0.1 wt % relative to the total weight of the positive electrode active material, and more preferably at least 0.15 wt % relative to the total weight of the positive electrode active material. In a preferred embodiment, the Si content of the silicon source is at most 1.0 wt % relative to the total weight of the positive electrode active material, preferably at most 0.5 wt % relative to the total weight of the positive electrode active material, and more preferably at most 0.1 wt % relative to the total weight of the positive electrode active material. In a preferred embodiment, the Si content of the silicon source is in the range of 0.05 and 1.0 wt % relative to the total weight of the positive electrode active material, preferably in the range of 0.1 and 0.5 wt % relative to the total weight of the positive electrode active material, and more preferably in the range of 0.15 and 0.1 wt % relative to the total weight of the positive electrode active material.

[0159] In a preferred embodiment of the process, the mixture is heated at a temperature of at least 25° C., preferably at least 50° C., more preferably at least 65° C. In a preferred embodiment of the process, the mixture is heated at a temperature of at most 450° C., preferably at most 400° C., more preferably at most 350° C. In a preferred embodiment of the process, the mixture is heated at a temperature between 25° C. and 450° C., preferably between 50° C. and 400° C., more preferably between 65° C. and 350° C.

[0160] In a preferred embodiment of the method, the mixture is heated for at least 2 hours, preferably at least 3 hours, more preferably at least 4 hours. In a preferred embodiment of the method, the mixture is heated for at most 15 hours, preferably at most 10 hours, more preferably at most 7 hours. In a preferred embodiment of the method, the mixture is heated for 2 to 15 hours, preferably 3 to 10 hours, more preferably 4 to 7 hours.

[0161] In a more preferred embodiment of the method

[0162] heating the mixture at a temperature between 25°C and 450°C, preferably between 50°C and 400°C, more preferably between 65°C and 350°C; and

[0163] • The mixture is heated for a period of 2 hours to 15 hours, preferably 3 hours to 10 hours, more preferably 4 hours to 7 hours.

[0164] A preferred embodiment of the method is to heat the mixture under an oxidizing atmosphere. Preferably, the oxidizing atmosphere comprises oxygen, such as air, or consists of oxygen.

[0165] In a more preferred embodiment, heating of the mixture is performed in a furnace under an oxidizing atmosphere.

[0166] Method characterization product

[0167] In a third aspect, the present invention relates to a positive electrode active material obtainable by the method according to the second aspect of the invention. As will be understood by the skilled person, all embodiments relating to the positive electrode active material according to the first aspect of the invention and / or the method according to the second aspect of the invention apply mutatis mutandis to the positive electrode active material obtainable by the method according to the invention. For example, the embodiments relating to Li, M', Si explained herein in the context of the positive electrode active material or the method for producing the positive electrode active material C 、Si A 、Si B The various embodiments for identification and amount of the silicon source also apply to the positive electrode active material obtainable by the method for preparing the positive electrode active material.

[0168] batteries

[0169] In a fourth aspect, the present invention relates to a battery comprising a positive electrode active material according to the first aspect of the invention and / or a positive electrode active material obtainable by a process according to the third aspect of the invention.

[0170] In a preferred embodiment, the battery is a solid-state battery.

[0171] In a particular preferred embodiment, the solid-state battery comprises a sulfide-based electrolyte. Preferably, the electrolyte is a sulfide-based solid electrolyte, and more preferably, the electrolyte comprises Li, P, and S. Generally, the following sulfur-containing compounds of Li6PS5X can be appropriately used, wherein X is F, Cl, Br, or I; preferably, X is Cl or Br, sulfo-LISICON (Li 3.25 Ge 0.25 P 0.75 S4), Li2S-P2S5-LiCl, Li2S-SiS2, LiI-Li2S-SiS2, Li2S-P2S5-LiCl, Li2S-SiS2, LiI-Li 2S-SiS2, LiI-Li2S-P2S5, LiI-Li2SP2O5, LiI-Li3PO4-P2S5, Li2S-P2S5, Li3PS4, Li7P3S 11 , LiI-Li2S-B2S3, Li3PO4-Li2S-SiS2, Li3PO4-Li2S-SiS2, Li3PO4-Li2S-SiS2, Li 10 GeP2S 12 、Li 9.54Si 1.74 P 1.44 S 11.7 Cl 0.3 and / or Li7P3S 11 In a highly preferred embodiment, the battery is a sulfide solid state battery.

[0172] In a particular preferred embodiment, the solid-state battery comprises a polymer-based electrolyte, preferably a polymer-based solid electrolyte, more preferably a polymer-based solid electrolyte is a polymer comprising ethylene oxide units, most preferably a polymer-based solid electrolyte is polyethylene oxide. The present invention is not limited to having a specific weight average molecular weight M w A specific polyethylene oxide. Such polymers are commercially available with many different number average molecular weights. Preferably, the polyethylene oxide has a weight average molecular weight M of less than 5 000 000 g / mol and greater than 50 000 g / mol. w , preferably a weight average molecular weight M of less than 3 000 000 g / mol and greater than 100 000 g / mol w , more preferably a weight average molecular weight M of less than 2 000 000 g / mol and greater than 500 000 g / mol w , most preferably a weight average molecular weight M of about 1 000 000 g / mol w In a highly preferred embodiment, the battery is a polymer solid state battery.

[0173] Preferably, the solid-state battery further comprises an anode comprising an anode active material. Suitable electrochemically active anode materials are those known in the art. For example, the anode may comprise graphite carbon, metallic lithium, or a metal alloy comprising lithium, such as a Li-In alloy, as the anode active material.

[0174] In a preferred embodiment, the battery according to the present invention, preferably a solid-state battery comprising a sulfide-based electrolyte as defined herein, has an efficiency of at least 85%, preferably at least 86%, more preferably at least 87%, most preferably at least 88%. As will be appreciated by the skilled person, the efficiency of a battery is determined where the initial charge capacity (CQ1) and the discharge capacity (DQ1) are within the range of 4.3 V to 2.5 V (Li / Li + ) or 3.7 V to 1.9 V (In-Li / Li + ) in constant current mode (CC) at a C rate of 0.1 C within a voltage range of 100 Ω. The efficiency (%) of the reversible capacity is given by the following equation:

[0175] .

[0176] Preferably, the protocol is defined using a 1C current of 160 mA / g.

[0177] A preferred embodiment relates to a battery according to the invention, preferably a solid-state battery comprising a polymer-based electrolyte as defined herein, having a Q of less than 70 mAh / g, preferably less than 65 mAh / g, more preferably less than 50 mAh / g, most preferably less than 45 mAh / g. 总量 As will be appreciated by those skilled in the art, the following coin cell test procedure is used to define Q within the 4.4–3.0 V / Li metal window using a 1C current definition of 160 mA / g. 总量 :

[0178] Step 1) Charge in constant current mode with a C rate of 0.05 and an end condition of 4.4 V, followed by a rest period of 10 minutes.

[0179] Step 2) Discharge in constant current mode with a C rate of 0.05 and an end condition of 3.0 V, followed by a 10-minute rest. The discharge capacity of this step is DQ1.

[0180] Step 3) Charge in constant current mode with a C rate of 0.05 and an end condition of 4.4 V.

[0181] Step 4) Switch to constant voltage mode and maintain 4.4 V for 60 hours.

[0182] Step 5) Discharge in constant current mode with a C rate of 0.05 and an end condition of 3.0 V. The discharge capacity of this step is DQ2,

[0183] where Q 总量 Defined as the total leakage capacity at high voltage and temperature in step 4).

[0184] use

[0185] In a fifth aspect, the present invention relates to the use of the positive electrode active material according to the first aspect of the invention and / or the positive electrode active material obtainable by the process according to the third aspect of the invention in a battery.

[0186] A preferred embodiment is the use of the positive electrode active material in a battery, preferably a solid-state battery, more preferably a sulfide solid-state battery, to increase the efficiency of said battery.

[0187] A preferred embodiment is the use of a positive electrode active material in a battery, preferably a solid-state battery, more preferably a polymer solid-state battery, to reduce the Q of said battery. 总量 .

[0188] In a sixth aspect, the present invention relates to the use of a battery according to the invention in any of a portable computer, a tablet computer, a mobile phone, an energy storage system, an electric vehicle or a hybrid electric vehicle, preferably in an electric vehicle or a hybrid electric vehicle.

[0189] Example

[0190] The following analytical methods were used in the examples:

[0191] A) Inductively Coupled Plasma-Optical Emission Spectrometry (ICP-OES)

[0192] The content of elements in the positive electrode active material examples and comparative examples described herein below was measured by inductively coupled plasma-optical emission spectroscopy (ICP-OES) using an Agilent ICP 720-OES. 1 gram of powder sample was dissolved in 50 mL of high purity hydrochloric acid in an Erlenmeyer flask. The flask was covered with a watch glass and heated at 380°C. ° Heat on a hot plate at 400 °C until the sample is completely dissolved. After cooling to room temperature, transfer the solution and the rinse water from the Erlenmeyer flask to a 250 mL volumetric flask. Then, fill the volumetric flask with deionized water to the 250 mL mark and mix thoroughly. Remove an appropriate amount of solution with a pipette and transfer it to a 250 mL volumetric flask for the second 次 The sample was diluted by filling a volumetric flask to the 250 mL mark with an internal standard and 10% hydrochloric acid, followed by homogenization. Finally, the solution was used for ICP-OES measurement. The contents of Ni, Mn, Co, and Si are expressed as wt% of the total amount of these contents. Another suitable solvent can be used to fully dissolve the positive electrode active material powder sample.

[0193] B) Particle size

[0194] After dispersing examples of positive electrode active material powders, such as those described herein below, in an aqueous medium, the PSD was measured using a Malvern Mastersizer 3000 equipped with a Hydro MV wet dispersion accessory. To improve the dispersion of the positive electrode active material powder examples, sufficient ultrasonic irradiation and stirring were applied, and an appropriate surfactant was introduced. D50 was defined as the particle size at 50% of the cumulative volume % distribution.

[0195] C) Polymer battery test

[0196] C1) Polymer battery preparation

[0197] C1.1) Preparation of solid polymer electrolyte (SPE)

[0198] The solid polymer electrolyte (SPE) was prepared as follows:

[0199] Step 1) Polyethylene oxide (PEO, 1,000,000 g / mol, Alfa Aesar) and lithium bis(trifluoromethanesulfonyl)imide (LiTFSI, >98.0%, TCI) were mixed in 99.8 wt% anhydrous acetonitrile (Aldrich) using a mixer at 2,000 rpm for 30 minutes. The mass ratio of polyethylene oxide to LiTFSI was 3.0.

[0200] Step 2) The mixture from step 1) was poured into a Teflon dish and dried at 25°C for 12 hours.

[0201] Step 3) Separating the dried SPE from the disc and punching the dried SPE to obtain an SPE disc with a thickness of 300 μm and a diameter of 19 mm.

[0202] C1.2) Positive electrode preparation

[0203] Prepare the positive electrode as follows:

[0204] Step 1) Prepare a polymer electrolyte mixture comprising a solution of polyethylene oxide (PEO, 100,000 g / mol, Alfa Aesar) in 99.7 wt% anisole (Sigma-Aldrich) and a solution of lithium bis(trifluoromethanesulfonyl)imide (LiTFSI, >98.0%, TCI) in acetonitrile. The weight ratio of PEO to LiTFSI in this mixture was 74:26.

[0205] Step 2) The polymer electrolyte mixture prepared in step 1) was mixed with a positive electrode active material and a conductor powder (Super P, Timcal) in an acetonitrile solution at a weight ratio of 21:75:4 to prepare a slurry mixture. The mixture was mixed using a homogenizer at 5,000 rpm for 45 minutes.

[0206] Step 3) The slurry mixture from step 2) was cast on one side of a 20 μm thick aluminum foil with a 100 μm coater gap.

[0207] Step 4) The slurry cast foil was dried at 30°C for 12 hours and then punched out to obtain catholyte electrodes with a diameter of 14 mm.

[0208] C1.3) Negative electrode preparation

[0209] Li foil (16 mm in diameter and 500 μm in thickness) was prepared as the negative electrode.

[0210] C1.4) Polymer battery assembly

[0211] Coin-type polymer cells were assembled in an argon-filled glove box in the following order from bottom to top: a 2032 coin cell can, the positive electrode prepared in Section C1.2, the SPE prepared in Section C1.1, a gasket, the negative electrode prepared in Section C1.3, a spacer, a wave spring, and a cell cover. The coin cell was then fully sealed to prevent electrolyte leakage.

[0212] C2) Test method

[0213] Each coin-type polymer cell was cycled at 80°C using a Toscat-3100 computer-controlled galvanostatic cycling station (Toyo). The coin cell test procedure was defined using a 1C current of 160 mA / g in the 4.4–3.0 V / Li metal window range according to the following protocol:

[0214] Step 1) Charge in constant current mode with a C rate of 0.05 and an end condition of 4.4 V, followed by a rest period of 10 minutes.

[0215] Step 2) Discharge in constant current mode with a C rate of 0.05 and an end condition of 3.0 V, followed by a 10-minute rest. The discharge capacity of this step is DQ1.

[0216] Step 3) Charge in constant current mode with a C rate of 0.05 and an end condition of 4.4 V.

[0217] Step 4) Switch to constant voltage mode and maintain 4.4 V for 60 hours.

[0218] Step 5) Discharge in constant current mode with a C rate of 0.05 and an end condition of 3.0 V. The discharge capacity of this step is DQ2.

[0219] Q 总量 Defined as the total leakage capacity at high voltage and temperature in step 4) according to the described test method. Q 总量 The low value of indicates the high stability of the positive electrode active material powder during high temperature operation.

[0220] D) Sulfide battery test

[0221] D1) Sulfide battery preparation

[0222] D1.1) Positive electrode preparation:

[0223] For the preparation of the positive electrode, a slurry containing a positive electrode active material powder, a Li-PS based solid electrolyte, carbon (Super-P, Timcal) and a binder (RC-10, Arkema) (a formulation of 64.0: 30.0: 3.0: 3.0 by weight) in butyl acetate solvent was mixed in an argon-filled glove box. The slurry was cast on one side of an aluminum foil, and the slurry-coated foil was then dried in a vacuum oven to obtain a positive electrode. The resulting positive electrode was punched out with a diameter of 10 nm, with an active material loading of approximately 4 mg / cm 2 .

[0224] D1.2) Negative electrode preparation:

[0225] For the preparation of the negative electrode, a Li foil (3 mm diameter, 100 μm thickness) was placed on the top center of an In foil (10 nm diameter, 100 μm thickness) and pressed to form a Li-In alloy negative electrode.

[0226] D1.3) Diaphragm preparation:

[0227] In order to prepare a separator that also functions as a solid electrolyte, the Li-PS-based solid electrolyte was pressed under a pressure of 250 MPa to obtain a pellet with a thickness of 100 μm.

[0228] D1.4) Battery Assembly:

[0229] The sulfide solid-state rechargeable battery was assembled in an argon-filled glove box in the following order: positive electrode (coated portion on top) containing an Al current collector, separator, negative electrode (Li side on top), and Cu current collector. The stack was pressed together at a pressure of 250 MPa and placed in an external cage to prevent exposure to air.

[0230] D2) Test methods

[0231] The test method was a conventional "constant cutoff voltage" test. Each cell was cycled at 60°C using a Toscat-3100 computer-controlled constant current cycling station (from Toyo).

[0232] The scheme is defined using a 1C current of 160 mA / g. The initial charge capacity (CQ1) and discharge capacity (DQ1) are in the range of 4.3 V to 2.5 V (Li / Li + ) or 3.7 V to 1.9 V (In-Li / Li + ) in constant current mode (CC) at a C rate of 0.1 C within a voltage range of 100 Ω. The efficiency (%) of the reversible capacity is given by the following equation:

[0233] .

[0234] E) Exposure test

[0235] Carbon and moisture exposure tests were performed by spreading 40 g of positive electrode active material evenly on a 95 x 95 mm 2 The positive electrode active material powder was taken out after 3 days (72 hours) for carbon analysis as described in Method E and moisture analysis as described in Method F.

[0236] F) Carbon Analysis

[0237] The carbon content of the positive electrode active material powder was measured using a Horiba Emia-Expert carbon / sulfur analyzer. One gram of the positive electrode active material powder was placed in a ceramic crucible in a high-frequency induction furnace. 1.5 grams of tungsten and 0.2 grams of tin were added to the crucible as promoters. The powder was heated at a programmable temperature, and the gases produced during combustion were then analyzed using an infrared detector. Analysis of CO2 and CO determined the carbon concentration.

[0238] G) Moisture analysis

[0239] The moisture content of the positive electrode active material powder was measured using a Karl Metrohm Fischer coulometer. 1 gram of the positive electrode active material powder was placed in a 200°C KF furnace under an N2 atmosphere. The evaporated moisture was directed to a KF reactor and analyzed by KF coulometric analysis.

[0240] H) X-ray photoelectron spectroscopy (XPS)

[0241] In the present invention, X-ray photoelectron spectroscopy (XPS) is used to analyze the surface of the positive electrode active material powder particles. In XPS measurements, signals are obtained from the top few nanometers (e.g., 1 nm to 10 nm) of the sample (i.e., the surface layer). Therefore, all elements measured by XPS are contained in the surface layer.

[0242] For surface analysis of the positive electrode active material powder particles, a Thermo K-α+ spectrometer was used for XPS measurements. Monochromatic Al Kα radiation (hυ=1486.6 eV) was used, the spot size was 400 μm, and the measurement angle was 45°. A wide survey scan was performed at a pass energy of 200 eV to identify the elements present on the surface. After data collection, the C1s peak with maximum intensity (or center) at a binding energy of 284.8 eV was used as the calibration peak position. Subsequently, a precise narrow scan was performed at 50 eV, and at least 10 scans were performed for each identified element to determine the precise surface composition.

[0243] Curve fitting was performed using CasaXPS version 2.3.19PR1.0 using Shirley-type background processing and Scofield sensitivity factors. The fitting parameters are shown in Table 2a. The line shape GL(30) is a Gaussian / Lorentzian product formula, where 70% is Gaussian and 30% is Lorentzian. LA(α,β,m) is an asymmetric line shape, where α and β define the peak tail extension and m defines the width.

[0244] Table 1a. XPS fitting parameters of Ni2p3, Mn2p3, Co2p3, and Si1p.

[0245]

[0246] For the Co peaks, set constraints for each defined peak according to Table 1b.

[0247] Table 1b. XPS fitting constraints for Co2p peak fitting.

[0248]

[0249] The Si surface content determined by XPS is expressed as the atomic fraction of Si in the surface layer of the particle divided by the total content of Ni, Mn, Co and / or Si in the surface layer. The calculation method is as follows:

[0250]

[0251] The present invention is further illustrated in the following examples:

[0252] Comparative Example 1

[0253] A single crystalline positive electrode active material, labeled CEX1, was prepared according to the following steps:

[0254] Step 1) Preparation of transition metal oxide hydroxide precursor: having a metal composition Ni 0.85 Mn 0.07 Co 0.08 Nickel-based transition metal oxyhydroxide powders (TMH1) were prepared by coprecipitation using mixed nickel-manganese-cobalt sulfate, sodium hydroxide, and ammonia in a large-scale continuous stirred tank reactor (CSTR).

[0255] Step 2) Precursor oxidation: The TMH1 prepared in step 1) was heated at 400° C. for 7 h in an oxidizing atmosphere to obtain a heated product.

[0256] Step 3) First Mixing: The heated product prepared from step 2) was mixed with LiOH in an industrial blender to obtain a first mixture having a lithium to metal (Ni, Mn and Co) ratio of 0.96.

[0257] Step 4) First heating: The first mixture from step 3) is heated at 890° C. for 11 hours in an oxidizing atmosphere to obtain a first heated product.

[0258] Step 5) Wet Bead Milling: The first heated product from step 4) was bead milled in a solution containing 0.5 mol% Co relative to the total molar content of Ni, Mn, and Co in the first heated product, followed by drying and sieving to obtain a milled product. The bead milling was performed at a weight ratio of solid to solution of 6:4 for 20 minutes.

[0259] Step 6) Second mixing: The milled product obtained from step 5) was mixed in an industrial blender with 1.5 mol % of Co from Co 3 O 4 and 7.5 mol % of Li from LiOH, each relative to the total molar content of Ni, Mn and Co in the milled product, to obtain a second mixture.

[0260] Step 7) Second Heating: The second mixture from step 6) was heated at 760° C. for 10 hours in an oxidizing atmosphere, then pulverized and sieved with 250 ppm alumina powder to obtain CEX1 containing Ni, Mn, and Co with a ratio of Ni:Mn:Co of 0.84:0.07:0.09 as obtained by ICP-OES. CEX1 had a D50 of 4 μm.

[0261] As a result of the wet milling in step 5), CEX1 is a single crystal powder (i.e. a powder comprising single particles and / or secondary particles, wherein each single particle consists of only one primary particle and each secondary particle consists of at least two primary particles and at most twenty primary particles).

[0262] Example 1

[0263] EX1.1 was prepared by mixing CEX1 with 2000 ppm of Si from trimethylsiloxy-terminated polydimethylsiloxane (PDMS-C) in an industrial blender, followed by heating at 75°C for 6 h under an oxygen flow. PDMS-C is a liquid with a molecular weight of approximately 410 g / mol.

[0264] EX1.2 was prepared according to the same method as EX1.1, except that the heating temperature was 150°C.

[0265] EX1.3 was prepared according to the same method as EX1.1, except that the heating temperature was 300°C.

[0266] Example 2

[0267] EX2.1 was prepared by mixing CEX1 with 2000 ppm of Si from hydroxyl-terminated polydimethylsiloxane (PDMS-O) in an industrial blender, followed by heating at 75°C for 6 hours under an oxygen flow. PDMS-O is a liquid with a molecular weight of approximately 4200 g / mol.

[0268] EX2.2 was prepared according to the same method as EX2.1, except that the heating temperature was 150°C.

[0269] EX2.3 was prepared according to the same method as EX2.1, except that the heating temperature was 300°C.

[0270] Comparative Example 2

[0271] The polycrystalline positive electrode active material, labeled CEX2.1, was prepared according to the following steps:

[0272] Step 1) Mixing: TMH1 prepared from step 1) of CEX 1 was mixed with LiOH in an industrial blender to obtain a first mixture with a lithium to metal (Ni, Mn and Co) ratio of 0.98.

[0273] Step 2) Heating: The first mixture from step 1) was heated at 785°C for 10 hours in an oxidizing atmosphere to obtain CEX2 containing Ni, Mn and Co in a ratio of Ni: Mn: Co of 0.85:0.07:0.08 as obtained by ICP-OES. CEX1 had a D50 of 4 μm.

[0274] CEX2.2 was prepared by mixing CEX2.1 with 2000 ppm of Si from PDMS-C in an industrial blender, followed by heating at 75 °C for 6 h under an oxygen flow.

[0275] CEX2.3 was prepared according to the same method as CEX2.2, except that the heating temperature was 150°C.

[0276] CEX2.4 was prepared according to the same method as CEX2.2, except that the heating temperature was 300°C.

[0277] Comparative Example 3

[0278] CEX3.1 was prepared by mixing CEX2.1 with 2000 ppm of Si from PDMS-O in an industrial blender, followed by heating at 75 °C for 6 h under an oxygen flow.

[0279] CEX3.2 was prepared according to the same method as EX2.1, except that the heating temperature was 150°C.

[0280] CEX3.3 was prepared according to the same method as EX2.1, except that the heating temperature was 300°C.

[0281] Example 3

[0282] Prepare EX3.1 according to the following steps:

[0283] Step 1) Mixing: 300 g of CEX1 and 2.97 g of methyltrimethoxysilane (CH3Si(OCH3)3) were mixed in an industrial blender.

[0284] Step 2) Heating: The mixture prepared from step 1) was heated at 350°C under an oxygen flow for 6 hours to produce EX3.1 with 2000 ppm Si.

[0285] Prepare EX3.2 according to the following steps:

[0286] Step 1) Preparation of methyltrimethoxysilane solution: Mix 2.97 g of methyltrimethoxysilane with 0.8 g of water

[0287] Step 2) Mixing: 300 g of CEX1, 9.7 g of water and the methyltrimethoxysilane solution prepared in step 1) were mixed in an industrial blender.

[0288] Step 3) Heating: The mixture prepared from step 2) was heated at 350° C. under an oxygen flow for 6 hours to produce EX3.2 containing about 2000 ppm Si.

[0289] EX3.3 was prepared according to the same method as EX3.2, except that 8.25 g of ethanol was used instead of water in step 2).

[0290] EX3.4 was prepared according to the same method as EX3.2, except that 0.30 g of methyltrimethoxysilane was mixed with 0.05 g of water in step 1, and 11.1 g of ethanol was used instead of water in step 2. EX3.4 contained about 200 ppm Si.

[0291] EX3.5 was prepared according to the same method as EX3.3, except that 0.74 g of methyltrimethoxysilane was mixed with 0.20 g of water in step 1, and 10.6 g of ethanol was used instead of water in step 2. EX3.5 contained about 500 ppm Si.

[0292] EX3.6 was prepared according to the same method as EX3.3, except that 1.48 g of methyltrimethoxysilane was mixed with 0.39 g of water in step 1, and 9.8 g of ethanol was used instead of water in step 2. EX3.6 contained about 1000 ppm Si.

[0293] result

[0294] Table 2. Summary of the processes and characteristics of CEX1, EX1.1-EX1.3, EX2.1-EX2.3, CEX2.1-CEX2.4, and CEX3.1-CEX3.3

[0295]

[0296] na=Not Available

[0297] Table 3. Summary of the process and characteristics of CEX1 and EX3.1-EX3.6

[0298]

[0299] na=Not Available

[0300] Tables 2 and 3 summarize the processes and characteristics of the Examples and Comparative Examples with variations in morphology, Si source, Si amount, and heating temperature. B or Si C The value indicates that Si exists on the surface of the positive electrode active material, and the signal of the XPS measurement is obtained from the first few nanometers (eg, 1 nm to 10 nm) of the uppermost portion (ie, surface layer) of the sample.

[0301] As can be seen from Table 2, the positive electrode active material having a single crystal morphology (i.e., having single particles and / or secondary particles, wherein each single particle consists of only one primary particle, and each secondary particle consists of at least two primary particles and at most twenty primary particles) and a combination of Si on the surface can better suppress the leakage capacity (Q) compared to the positive electrode active material having a polycrystalline morphology. 总量 ). In addition, for the positive electrode active material comprising single crystal morphology and Si on the surface, lower carbon levels were observed after the 3-day exposure test.

[0302] In Table 3, the morphology of the positive electrode active materials is all single crystal, and methyltrimethoxysilane is used as the Si source. Additional benefits are observed in lower moisture levels after 3 days of exposure testing, and improved efficiency is observed in the sulfide cells.

Claims

1. A positive electrode active material for a solid-state battery, the positive electrode active material comprising lithium, oxygen, nickel, and at least one metal selected from manganese and cobalt, wherein the positive electrode active material further comprises Si in an amount measured by XPS analysis B of silicon, of which Si B It is expressed as the ratio of the mole fraction of Si to the sum of the mole fractions of Ni, Mn, Co and Si. Among them Si B >0.05, and wherein the positive electrode active material comprises single crystal particles.

2. The positive electrode active material according to claim 1, the positive electrode active material further having a carbon content in the range of 150 ppm to 2000 ppm of the total weight of the positive electrode active material, preferably a carbon content in the range of 250 ppm to 1850 ppm, more preferably a carbon content in the range of 300 ppm to 1700 ppm of the total weight of the positive electrode active material, the carbon content being measured by a carbon analyzer.

3. The positive electrode active material according to claim 1 or 2, wherein Si B In the range of 0.1 and 1.0, preferably Si B In the range of 0.15 and 0.98, more preferably Si B In the range of 0.2 and 0.

9.

4. The positive electrode active material according to any one of the preceding claims, wherein the positive electrode active material further comprises Si in an amount of C of silicon, of which Si C It is expressed as the ratio of the molar fraction of Si to the sum of the molar fractions of Ni, Mn and Co, where Si C In the range of 0.10 and 50.0, preferably Si C In the range of 0.15 and 15.0, more preferably Si C In the range of 0.20 and 1.

0.

5. The positive electrode active material according to any one of the preceding claims, the positive electrode active material comprising Li, Ni, Mn, Co, and oxygen, wherein: - Ni with a content of x, wherein 50.0 mol% ≤ x ≤ 98.0 mol% relative to the sum of Ni, Mn, and Co, - Mn with a content of y, wherein 0.0 mol% ≤ y ≤ 30.0 mol% relative to the sum of Ni, Mn, and Co, - Co with a content of z, wherein 0.0 mol% ≤ z ≤ 30.0 mol% relative to the sum of Ni, Mn, and Co, - wherein x, y, and z are measured by ICP-OES.

6. The positive electrode active material according to claim 5, the positive electrode active material comprising Li, M', and oxygen, wherein M' includes: - Ni with a content of x', wherein 50.0 mol% ≤ x' ≤ 98.0 mol% relative to M', - Mn with a content of y', wherein 0.0 mol% ≤ y' ≤ 30.0 mol% relative to M', - Co with a content of z', wherein 0.0 mol% ≤ z' ≤ 30.0 mol% relative to M', - Si with a content of a', wherein 0.0 mol% < a' ≤ 5.0 mol% relative to M', - D with a content of d', wherein D is an element other than Li, Ni, Mn, Co, Si, and oxygen; wherein 0.0 mol% ≤ d' ≤ 2.0 mol% relative to M', - wherein x', y', z', a', and d' are measured by ICP-OES, and - wherein x' + y' + z' + a' is 100.0 mol%.

7. The positive electrode active material according to claim 6, wherein the positive electrode active material has a Si content Si defined as a' / (x'+y'+z'+a') A , where the ratio Si B / Si A >5.

0.

8. The positive electrode active material according to claim 7, wherein the ratio of Si B / Si A >10.0, preferably where the ratio Si B / Si A >15.0, more preferably wherein the ratio Si B / Si A >20.

0.

9. The positive electrode active material according to any one of claims 6 to 8, wherein 55.0 mol% ≤ x' ≤ 90.0 mol% relative to M', preferably 58.0 mol% ≤ x' ≤ 88.0 mol%, more preferably 60.0 mol% ≤ x' ≤ 85.0 mol%.

10. The positive electrode active material according to any one of claims 1 to 9, the positive electrode active material having a carbon absorption amount less than 1500 ppm carbon of the total weight of the positive electrode active material, preferably a carbon absorption amount less than 1200 ppm carbon, more preferably a carbon absorption amount less than 1000 ppm carbon of the total weight of the positive electrode active material, wherein the carbon absorption amount is measured by an exposure test.

11. A method for producing a positive electrode active material, preferably a positive electrode active material according to any one of claims 1 to 10, wherein the method comprises: Step a) mixing a lithium transition metal-based oxide compound with a silicon source, and Step b) heating the mixture in a furnace under an oxidizing atmosphere at a temperature below 500° C. for a period of time between 1 hour and 20 hours to obtain the positive electrode active material. 12 . The method according to claim 11 , wherein the Si source is a silicon alkoxide, an alkylalkoxysilane or a polysiloxane, preferably an alkylalkoxysilane or a polysiloxane. 13 . A solid-state secondary battery comprising the positive electrode active material according to claim 1 . 14 . The solid-state battery according to claim 13 , comprising a polymer-based solid electrolyte or a sulfide-based solid electrolyte.

15. Use of the solid-state battery according to 13 or 14 in any one of a portable computer, a tablet computer, a mobile phone, an energy storage system, an electric vehicle or a hybrid electric vehicle.